A Case of Post Viral Acute Longitudinal Extensive Transverse Myelitis (LETM): MOGAD- A New Horizon (Bangladesh Critical Care Journal, 2024)
Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a recently identified autoimmune disorder that presents in both adults and children. It is a group of central nervous system demyelinating diseases caused by auto antibodies against myelin oligosaccharide protein, a myelin sheath component protein, and present with a variety of symptoms, including optic neuritis, longitudinal extensive transverse myelitis (LETM), acute disseminated encephalomyelitis (ADEM), brainstem encephalitis, and corticobasal encephalitis. Although there are clinical phenotypic overlaps between MOGAD, multiple sclerosis, and aquaporin-4 antibody-associated neuromyelitis optica spectrum disorder (NMOSD) cumulative biological, clinical, and pathological evidence discriminates between these conditions. Here, we present a case of a young male with acute onset of spastic paraplegia with sphincters involvement and patchy loss of pinprick sensation with positive Anti-MOG Antibody shortly after viral febrile illness.Bangladesh Crit Care J March 2024; 12 (1): 62-67